Bibliometric and altmetric analysis of publications examining education methods in realm of anatomy - Petekkaya, Emine; Karadağ, Mehmet; Dokur, Mehmet (The European Research Journal, 2021)
Objectives: This study aimed to investigate the significance of publications examining the effectiveness of education methods in the field of anatomy with the method of bibliometric and altmetric analysis, as well as online attention levels. Methods: To search all publications, “Anatomy education” was entered as a search term on the Web of Science database. The topics, journal impact factors, publication years and research centers of the first 100 articles with the highest numbers of citations were examined, and their analysis was conducted with the “Altmetric it on website: http: almetric.com”. Results: Four thousand, three hundred fifty-six articles published in the period of 1975-2019 containing the key phrase “Anatomy education” were found on Web of Science. The study with the highest number of citations was the study published by McLachlan et al. titled “Teaching anatomy without cadavers, 2004”. It was observed that the study titled “The production of anatomical teaching resources using three-dimensional (3D) printing technology, 2014” was the article with the highest rate of sharing on Twitter with the highest altmetric attention score (AAS) value. The AAS rates varied between 130 and 0. Conclusions: Bibliometric and altmetric analysis provides significant but different points of view regarding the effects of an article in the world of science. The altmetrics score may provide contributions in determining the direction of studies regarding the high-level interests and perceptions of the public on dynamic science and the field of medicine.